A novel software framework for magnetic particle imaging reconstruction. Issue 4 (31st January 2022) - Shen, Yusong; Hu, Chaoen; Zhang, Peng; Tian, Jie; Hui, Hui
Abstract: Magnetic particle imaging is a novel tomographic imaging technique that enables noninvasive and highly sensitive imaging of superparamagnetic iron oxide nanoparticles distributed in living subjects. Several studies have reported on the development of reconstruction algorithms; however, a unified software framework for magnetic particle imaging reconstruction has yet to be developed. Herein, we propose a high‐performance, flexible, and easy‐to‐use magnetic particle imaging reconstruction framework using the Python programming language. The magnetic particle imaging reconstruction framework consists of the data access, preprocessing, image reconstruction, and postprocessing phases. We used the proposed framework to simulate the x‐space and system matrix‐based reconstruction methods with Cartesian and Lissajous scan trajectories. The reconstruction results of an open magnetic particle imaging dataset and a numerically simulated phantom demonstrated that the magnetic particle imaging reconstruction framework provides a reliable and accessible environment for magnetic particle imaging reconstruction, which can be extended and customized.